Perlindungan Hukum Bagi Konsumen Pada Makanan Kadaluarsa di Kota Samarinda - Imelda Hasibuan; Eli Tri Kursiswanti; Muhammad Japri; Henny Maulida (LPPM STIH Awang Long, 2022)
The implementation of legal protection for consumers regarding expired food in the city of Samarinda has not been maximized, because there is still a lot of food past the expiration date that is still circulating on the market, in this case the Ministry of Health through the Balai POM Deperindag Kop and Non-Departmental Agencies when carrying out inspections still find a lot of expired food circulating in the market, and can endanger the health of humans who consume them. In this paper the author uses a normative juridical approach, because of this approach, this model of legal research is called normative legal research. Legal provisions are the primary legal material for Law No. 8 of 1999 concerning Consumer Protection. The author uses the library research method or literature review. This library research research is to conduct research from library books, magazines, journals and articles and sources from the internet that are relevant to the issues discussed.